Penerapan Extreme Programming dalam Pengembangan Sistem Informasi Pelayanan Publik PuspaBang di Kementerian Agama Kabupaten Bangli - Putra, I Putu Andika Subagya; Bagiarta, I Komang; Hendrawan, I Komang Risky (Unversitas Muhammadiyah Mataram, 2025)
Abstract: This study aims to develop the PuspaBang public service information system at the Office of the Ministry of Religious Affairs, Bangli Regency, employing the Extreme Programming (XP) methodology. XP was selected due to its emphasis on close collaboration between developers and stakeholders, as well as its capacity to accommodate rapidly evolving requirements. The system is implemented using the Laravel framework and MySQL database to ensure efficient data management. The development process follows an iterative cycle, incorporating continuous testing and refinement with active user participation. Functional verification was conducted through Black Box Testing, assessing core features including login, registration, application processing, data management, agenda management, and other related functions. The results demonstrate that the PuspaBang system operates in accordance with the specified requirements, without any functional failures, effectively managing service requests and fulfilling user expectations. Consequently, this development successfully delivers a responsive, stable, and reliable information system that supports religious service administration in Bangli Regency, providing significant benefits to both the community and the internal operations of the Ministry of Religious Affairs office.Abstrak: Penelitian ini bertujuan mengembangkan sistem informasi pelayanan publik PuspaBang di Kantor Kementerian Agama Kabupaten Bangli menggunakan metode Extreme Programming (XP). Metode XP dipilih karena menekankan kolaborasi erat antara pengembang dan pemangku kepentingan serta mampu beradaptasi dengan perubahan kebutuhan secara cepat. Sistem dikembangkan menggunakan framework Laravel dan basis data MySQL untuk pengelolaan data yang efektif. Proses pengembangan dilakukan secara iteratif dengan pengujian dan perbaikan berkelanjutan bersama pengguna. Tahap pengujian menggunakan metode Black Box Testing untuk memastikan fungsionalitas sistem tanpa melihat kode internal. Pengujian mencakup fitur utama seperti login, registrasi, pengelolaan permohonan, data, agenda, dan fitur lainnya. Hasil pengujian menunjukkan sistem PuspaBang berfungsi sesuai spesifikasi tanpa gangguan, mampu menangani permohonan layanan dengan lancar, dan memenuhi kebutuhan pengguna. Dengan demikian, pengembangan sistem ini berhasil menciptakan layanan yang responsif, stabil, dan andal untuk mendukung pelayanan keagamaan di Kabupaten Bangli, memberikan manfaat bagi masyarakat dan internal Kementerian Agama Kabupaten Bangli.